2019
DOI: 10.1055/s-0039-1688533
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Denture Base Thicknesses and Reinforcement on Fracture Strength in Mandibular Implant Overdenture with Bar Attachment: Under Various Acrylic Resin Types

Abstract: Objective This study aimed to assess the effect of reinforcement, denture base thickness, and acrylic resin types on dynamic and static fracture strength in mandibular implant overdentures with bar attachment. Materials and Methods One hundred and eight experimental mandibular implant overdentures with bar attachments were fabricated in three main groups, namely unreinforced (control: C), reinforced with unidirectional glass fibers (FR), and Co–Cr cast metal (MR). Each group included denture bases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Therefore, our observation that the fractures occurred around the area of the implants supports previous similar studies in the literature 4,23 . This can be explained by the large space occupied by the attachment housing, the subsequent decrease in denture base thickness, and the fact that most of the denture base material in that area was composed of auto‐cured resin used for attachment pick‐up procedures, as described by a previous study 24 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, our observation that the fractures occurred around the area of the implants supports previous similar studies in the literature 4,23 . This can be explained by the large space occupied by the attachment housing, the subsequent decrease in denture base thickness, and the fact that most of the denture base material in that area was composed of auto‐cured resin used for attachment pick‐up procedures, as described by a previous study 24 …”
Section: Discussionsupporting
confidence: 91%
“…4,23 This can be explained by the large space occupied by the attachment housing, the subsequent decrease in denture base thickness, and the fact that most of the denture base material in that area was composed of auto-cured resin used for attachment pick-up procedures, as described by a previous study. 24 As confirmed by previous studies, 5,6 a large number of technical procedures had to be undertaken to maintain the overdentures in function over 1 year. However, in our study, there were no differences in the total number of maintenance events between the two implant diameter groups.…”
Section: Discussionmentioning
confidence: 69%
“… 27 Reducing the denture base thickness to less than 2.0 mm has been reported to adversely affect flexural strength as the load bearing capacity decreases. 9 28 29 In this study, the addition of nano-ZrO 2 to PMMA denture base material was shown to provide significant improvement in the flexural strength even when the specimen's thickness was decreased. Incorporating nano-ZrO 2 has been previously reported to improve flexural strength values, 17 30 which could be attributed to the fact that nanoparticles may fill the spaces between polymeric chains.…”
Section: Discussionmentioning
confidence: 78%
“…Some situations indicate a thin denture base, such as tooth- or implant-supported overdenture, where the part over the abutment is weak and likelier to break. 9 28 Also, in cases where the patient has a sensitive gag reflex, the reflex will be stimulated by the thick maxillary denture base at the posterior area. 4 26 Moreover, some patients may encounter tongue restriction and distorted speech due to the thick denture base.…”
Section: Discussionmentioning
confidence: 99%
“…Metal reinforcement by; gold alloys, cobaltchromium and cobaltchrome-molybdenum alloys is most commonly used for reinforcement of acrylic denture bases and overdentures as well to resist masticatory forces and show less deformations and fracture. They become stronger with more resistance to masticatory forces and lighter in weight, although possibility to allergy sometimes can't be neglected (9) . Over last years, PEEK (poly ether ketone) material had emerged in the medical fields with tissue compatible, non-cytotoxic and thermally insulating properties (10) .…”
Section: Introductionmentioning
confidence: 99%